Rancang Bangun Pengendali dan Pemantau Suhu pada Dua Inkubator Telur Ayam Otomatis - Rudi Darmawan; Sri Ratna Sulistiyanti; Syaiful Alam (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
In this research, it was designed a temperature controller and monitoring system of two automatic chicken eggs incubator. Based on references, hatched chicken eggs require temperature 38oC-40oC and relative humidity about 55-65%. The temperature sensor used is LM 35 and humidity sensor used is DHT 11. Temperature controller uses microcontroller ATmega 328 P. The temperature is controlled by switching on/off method on incandescent bulbs used as heating tool and DC fan as cooling tool. Monitoring system uses a computer with LabVIEW software and LCD 16x2 for incubator. Wheel shelf of eggs will automatically rotate egg on 06.00 A.M. at 0o and 18.00 P.M. at 60o using servo motor. Communication used by two incubator to transmit data to computer is uses I2C method. LM35 temperature sensor is calibrated by using thermometer and the obtained error is 0.285714%, while DHT 11 humidity sensor is calibrated by Hygrometer and the obtained error is 1.5%. The result of system test shows that the average stability of temperature on incubator 1 and 2 is 39.01oC and the average humidity is 60%. Incubator monitoring system of temperature and humadity is displayed with real time uses LabVIEW software. Keywords: eggs incubator, controlling, monitoring, temperature, ATmega 328P